ASSOCIATION BETWEEN ULTRASOUND SIGNS OF JOINT INFLAMMATION AND RADIOGRAPHIC PROGRESSION IN PATIENTS WITH RHEUMATOID ARTHRITIS - O. G. Alekseeva; M. V. Severinova; A. V. Smirnov; N. V. Demidova; E. N. Aleksandrova; A. A. Novikov; E. L. Luchikhina; D. E. Karateev; S. I. Glukhova; A. V. Volkov; E. L. Nasonov (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is a chronic inflammatory disease causing joint destructive changes and disability.Objective: to investigate the association between the ultrasound signs of active inflammation and destruction of the joints, as evidenced by radiography, in RA patients treated with a treat-to-target strategy and to study whether ultrasound study (USS) of the joints can be used to predict the occurrence of their destructive changes.Subjects and methods. The investigation included 81 patients (medium age 56 [46; 62] years) with RA, who had been followed up at the V.A. Nasonova Research Institute of Rheumatology within the first Russian strategic study of pharmacotherapy for RA – REMARCA (Russian invEstigation of MethotrexAte and biologicals for eaRly aCtive Arthritis). In all the patients, methotrexate (Metoject, MEDAS, Germany) as the first disease-modifying anti-rheumatic drug was subcutaneously injected at an initial dose of 10 mg/week with its rapid escalation up to 20–25 mg/week. Then the therapy was added by biologicals as the need arose. Clinical and laboratory parameters were analyzed immediately before and then after 12, 24, 36, and 48 weeks. Efficacy was assessed using the European League Against Rheumatism (EULAR) criteria, CDAI, and SDAI. USS of eight articular areas (the wrist, second and third metacarpophalangeal, second and third proximal interphalangeal, second and fifth metatarsophalangeal joints) in the hand and foot of the clinically dominant side was carried out in all the patients before treatment and then after 12, 24, 36, and 48 weeks. Semiquantitative gray-scale (GS) assessment and power Doppler (PD) were performed. Radiographic examination was done before and after 48 weeks of therapy. The Sharp method modified by van der Heijde was employed to estimate X-ray changes.Results and discussion. In the group of patients with radiographic progression, the activity of inflammation, as evidenced by PD USS, was significantly higher at 48 weeks of the follow-up; at the same time, the median PD score was 0 in the absence of progression. At 48 weeks, radiographic progression was significantly more common in the group of patients with persistently active synovitis than in the group without inflammation (odds ratio (OR) 4.76; 95% confidence interval (CI) 1.2–18.9; р = 0.018). At 48 weeks of therapy, the PD score of 0 (complete lack of vascularization in the study joints) had satisfactory sensitivity (77%) and satisfactory specificity (59%) (the area under the curve was 0.698; p < 0.024; 95% CI 0.544–0.852). Multivariate analysis showed that GS USS scores after 24 weeks of therapy proved to be significant predictors of progressive erosive joint changes at 48 weeks of therapy (OR = 0.15; 95% CI, 0.023–0.207; p = 0.015). At the same time, the PD score following 24 weeks of therapy could not predict joint destruction (OR = 0.104; 95% CI, -0.043 to 0.251; р = 0.16). Clinical disease activity indices and baseline PD and GS scores were of no significant prognostic value.Conclusion. We found a significant association of radiographic progression with active synovitis, as evidenced by PD USS at 48 weeks of therapy; however, we did not obtain any convincing evidence for the prognostic value of the baseline ultrasound signs of inflammation.